The Impact of Learning from Different Viewing Angles on the Performance of Selected Rhythmic Gymnastics Skills Among Primary School Students - Khaleel Abdulqader, Neran (STKIP PGRI SUMENEP, 2025)
Motor learning is important in rhythmic gymnastics, which demands precision, coordination, and spatial awareness for the effective execution of the skill. The aim of this research is to analyse how various angles of objective presentation affect chosen rhythmic gymnastics skills acquisition and performance of primary school pupils. The study used?quasi-experimental research design, consisting of 42 fifth-grade male students, and divided them into an experimental and a control group. The experimental group was trained using the multi-angle view, while the control group was trained by conventional teaching methods. Data Collection and Analysis Pre-test?and post-test assessments were carried out and scored by expert judges using a standardised scoring rubric. To assess the intervention efficacy, paired sample t-tests and independent sample t-tests were computed. The study found that multi-angle learners significantly outperformed their traditional peers in executing skills. These results highlight how multimodal visuospatial training can promote motor skills learning. This study aims to promote the use of new cognitive?instructional strategies to enhance the acquisition of motor skills, enriching the panorama of sports teaching. Future research could investigate long-term retention effects, as well as the benefits of integrating advanced technologies such as virtual and augmented?reality in rhythmic gymnastics training.